Retreatment With Sofosbuvir Plus Grazoprevir/Elbasvir Plus Ribavirin of Patients With Hepatitis C Virus Genotype 1 or 4 Who Previously Failed an NS5A- or NS3-Containing Regimen: The ANRS HC34 REVENGE Study. (25th October 2017) - de Lédinghen, Victor; Laforest, Claire; Hézode, Christophe; Pol, Stanislas; Renault, Alain; Alric, Laurent; Larrey, Dominique; Métivier, Sophie; Tran, Albert; Jézéquel, Caroline; Samuel, Didier; Zoulim, Fabien; et al.
Abstract: Background: Failure to achieve sustained virological response (SVR) with hepatitis C virus (HCV) direct-acting antiviral (DAA)–based regimens is commonly associated with emergence of resistance-associated substitutions (RASs). Retreatment of patients who failed prior DAAs remains challenging. The aim of this prospective and randomized study was to evaluate the efficacy (primary endpoint: SVR 12 weeks after end of treatment [SVR12 ]) and safety of sofosbuvir + grazoprevir/elbasvir + ribavirin for 16 or 24 weeks in patients who had failed to achieve SVR on previous NS5A- or NS3-based therapy and with evidence of RASs at failure. Methods: Patients were chronically infected with HCV genotype 1 or 4. Most of them had advanced fibrosis or compensated cirrhosis (liver stiffness 5.8–48.8 kPa). Results: All patients achieved HCV RNA below the lower limit of quantification (either target detected [unquantifiable] or target not detected) during treatment. SVR12 was achieved by 25 of 26 patients. The only patient who did not reach SVR was a patient who died, but HCV RNA was negative at this time (5 weeks after stopping treatment). No patient discontinued treatment because of adverse events or virological failure. Globally, treatment was well tolerated. Conclusions: Our findings support the concept of retreating with sofosbuvir + grazoprevir/elbasvir + ribavirin, for 16 weeks, genotype 1 or 4 DAA-experienced patients with proven NS5A or NS3 RASs. Clinical Trials Registration: NCT02647632 Abstract : Our findings support the concept of 16 weeks of retreatment with sofosbuvir + grazoprevir/elbasvir + ribavirin for genotype 1 or 4–infected, direct-acting antiviral–experienced patients with proven NS5A or NS3 resistance-associated substitutions.